Peran Tim PKK Dalam Meningkatkan Kualitas Sumber Daya Manusia Di Desa Bicak Kecamatan Trowulan Kabupaten Mojokerto - Hikmah Muhaimin; Santosa; Dian Wijaya (Government Studies Departement of Universitas Islam Majapahit, Indonesia, 2020)
PKK is a community movement that has been active as a government partner in the implementation of various programscommunity development. The PKK has a main role, namely the driving force that empowers the potential of women to play an active role indevelopment and as an institution with the main mission of realizing a prosperous, advanced and independent family with more and more work achievements,has received recognition of its existence in the midst of society. With its core relation to owning and implementing the 10 main PKK programswhich has been institutionalized and accepted by the community because it is in accordance with the demands of life and people's livelihoods in improvingthe physical and spiritual welfare of the community as seen from social capital from the implementation of health, education and skills. The purpose ofThis research is to find out social capital as measured by indicators of trust, activities and to find out the benefits of implementing the PKK programin the field of health and education skills PKK Bicak Village, Trowulan District, Mojokerto Regency